Event overview: Promotion of Christian Takoffâ€™s books â€œTruth and Justiceâ€ and â€œChristalsâ€ - Marcheva, Deyana (Law Journal of New Bulgarian University, 2021)
In 2019 SIBI Publishing House issued two book collections of the interviews, public speeches, comments and other texts from the personal blog of the most prominent jurist Mr. Christian Takoff. His colleagues and friends â€“ the lawyer Mr. Valentin Braykov, the journalist Ms. Rossitsa Mihova and the judge Mr. Kalin Kalpakchiev delivered speeches at the event, which the Law Journal publishes with their consent.